2020
DOI: 10.1038/s41586-020-2174-3
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 inflammasome surveillance of DNA damage shapes neurodevelopment

Abstract: Neurodevelopment is characterized by rapid rates of neural cell proliferation and differentiation followed by a period of massive cell death where over half of all recently generated brain cells are pruned back. Large amounts of DNA damage, cellular debris, and byproducts of cellular stress are generated during these neurodevelopmental events, all of which can potentially activate immune signaling. How the immune response to this collateral damage influences brain maturation and function currently remains poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 40 publications
6
111
0
1
Order By: Relevance
“…In particular, MIA on the window from E12.5 to E14.5 during gestation may be critical stage for neurodevelopment in fetus. In fact, poly(I:C) injection on E12.5 results in strong induction of IL-17A at E14.5 that promotes ASD-like phenotypes of offspring [4,12]. In this study, we induced MIA on E14.0 by injecting LPS and demonstrated that bacterial-induced maternal IL-17A pathway by LPS promoted ASD-like behaviors of offspring.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In particular, MIA on the window from E12.5 to E14.5 during gestation may be critical stage for neurodevelopment in fetus. In fact, poly(I:C) injection on E12.5 results in strong induction of IL-17A at E14.5 that promotes ASD-like phenotypes of offspring [4,12]. In this study, we induced MIA on E14.0 by injecting LPS and demonstrated that bacterial-induced maternal IL-17A pathway by LPS promoted ASD-like behaviors of offspring.…”
Section: Discussionmentioning
confidence: 58%
“…MIA model to mimic viral infection has been frequently used by injecting one dose of poly(I:C) on embryonic day 12.5 (E12.5), which corresponds to the first trimester stage in human [5]. Recent MIA model by poly(I:C) injection has shown that pro-inflammatory cytokine interleukin 17A (IL-17A) produced by T helper 17 (Th17) cells plays a critical role in ASD-like phenotypes of offspring [4,10,12] and affects fetal brain development by generating cortical patches on cerebral cortex, which is associated with ASD-like behavioral abnormalities [32]. In addition, recent reports have indicated that maternal intestinal bacteria that promote Th17 cell differentiation regulate ASD-like phenotypes of MIA offspring [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our laboratory and others have shown the loss of Aim2 impacts neuronal morphology and negatively influences several behaviors such as anxiety and memory. 217,218 Furthermore, our recent studies demonstrate that defects in the AIM2 inflammasome can alter neurodevelopment. 217 Thus, it is feasible that changes in brain development existing before Aβ deposition may influence disease outcomes in AD mouse models.…”
Section: Role Of Inflammasomes In Admentioning
confidence: 97%
“…217,218 Furthermore, our recent studies demonstrate that defects in the AIM2 inflammasome can alter neurodevelopment. 217 Thus, it is feasible that changes in brain development existing before Aβ deposition may influence disease outcomes in AD mouse models. Moving forward, it will be interesting to revisit the role of the AIM2 inflammasome in AD using approaches that conditionally ablate AIM2 signaling following neurodevelopment.…”
Section: Role Of Inflammasomes In Admentioning
confidence: 97%
“…AIM2 inflammasome activation in response to genotoxic stress during neurodevelopment contributes to normal brain development by purging unfit neurons via GSDMDmediated pyroptosis. As a result, AIM2 deficiency leads to the retention of more cells (damaged as well as normal) in the brain and the development of anxiety-related behaviors in mice 67. In addition to cell-intrinsic DNA, cell-extrinsic DNA can also become mislocalized in the cytosol, thus becoming a ligand for AIM2.Phagocytic cells, such as macrophages, internalize cell-free DNA released upon cellular damage, self-DNA-immune complexes, and apoptotic bodies containing DNA.…”
mentioning
confidence: 99%